Energy‐Efficient Solar Photochemistry with Luminescent Solar Concentrator Based Photomicroreactors. Issue 40 (23rd August 2019) - Cambié, Dario; Dobbelaar, Jeroen; Riente, Paola; Vanderspikken, Jochen; Shen, Chong; Seeberger, Peter H.; Gilmore, Kerry; Debije, Michael G.; Noël, Timothy
Abstract: The sun is the most sustainable light source available on our planet, therefore the direct use of sunlight for photochemistry is extremely appealing. Demonstrated here, for the first time, is that a diverse set of photon‐driven transformations can be efficiently powered by solar irradiation with the use of solvent‐resistant and cheap luminescent solar concentrator based photomicroreactors. Blue, green, and red reactors can accommodate both homogeneous and multiphase reaction conditions, including photochemical oxidations, photocatalytic trifluoromethylation chemistry, and metallaphotoredox transformations, thus spanning applications over the entire visible‐light spectrum. To further illustrate the efficacy of these novel solar reactors, medicinally relevant molecules, such as ascaridole and an intermediate of artemisinin, were prepared as well. Abstract : Harvest time : A luminescent solar concentrator (LSC) based photomicroreactor harvests solar energy for applications in visible‐light‐mediated photochemistry. It can be applied to photochemical oxidations, photoredox catalysis, and metallaphotoredox couplings, spanning the entire visible‐light spectrum. The reactors are easily scaled, inexpensive, and self‐powered, making them ideally suited for the cost‐effective production of chemicals using solar energy.